PENGEMBANGAN POTENSI WISATA RELIGI MAKAM MEDANA SEBAGAI WISATA ALTERNATIF DI KABUPATEN LOMBOK UTARA - Andi Alfian ABT; Fathurrahim Fathurrahim; Agusman Agusman (Journal Of Responsible Tourism, 2022)
This research concerns the development of the potential of Medana tomb religious tourism as an alternative tourism in North Lombok Regency. The purpose of this study was to describe the development of the potential of Medana tomb religious tourism as an alternative tourism in North Lombok Regency. The research method used is descriptive qualitative with the research location in the Medana tomb. The data collection technique used observation, interview and documentation techniques related to potential development. Data analysis techniques used are data collection, data presentation, data reduction and drawing conclusions. The results of this study indicate that the potential development in the Medana tomb has not met the 4A components, namely attractions, accessibility, amenities and ancilarray. However, there are several existing components such as attractions and ancilarrays, but they have not been developed optimally due to lack of coordination from related institutions so that it becomes an obstacle in the development of the Medana tomb. Meanwhile, the Medana tomb has met the criteria of alternative tourism where alternative tourism prioritizes biotic and abiotic environmental aspects, namely with the taboo that should not damage the environment in the Medana tomb.